Dead things are closer than they appear - Wasley, Robin (Simon & Schuster Books for Young Readers, 2024)
Seventeen-year-old Sid lives in a tourist town where magic lies buried beneath the earth, but other than that, has a completely ordinary existence, until one day her brother goes missing and the ground opens up, unleashing the magic and zombies within.